The relationships between social support, medication adherence, and glycemic control among inpatients with type 2 diabetes: a cross-sectional survey in Xi’an, China - Haiyan Li; Hui Min; Lu Zhang; Youjia Li; Jing Wang; Xiaoni Jia (Frontiers in Pharmacology)
BackgroundSocial support may be important in the management of type 2 diabetes. This study aimed to investigate the relationships between social support, medication adherence, and glycemic control in Northwestern China.MethodsA cross-sectional questionnaire-based survey was carried out in the department of endocrinology in three teaching hospitals between February 2023 and April 2025. The Social Support Rating Scale (SSRS) was used to assess social support. The Adherence to Refills and Medications Scale (ARMS) was used to assess adherence to antidiabetic medications. Logistic regression analyses were performed to identify the factors associated with medication nonadherence and poor glycemic control. Receiver operating characteristic (ROC) was used to assess the performance of the logistic regression model in predicting medication nonadherence.ResultsA total of 522 inpatients finished the questionnaires, 323 (61.9%) inpatients were nonadherent to antidiabetic medications and the prevalence rate of poor glycemic control was estimated to be 82.6%. According to the multivariable logistic regression analysis, inpatients who had received low levels of social support had 2.48 times (95% CI = 1.419–4.322) greater odds of nonadherence to antidiabetic medications than those received high levels of social support, while inpatients who were underweight had 2.78 times (95% CI = 1.054–7.330) greater odds of nonadherence to antidiabetic medications than those with normal BMI. We found that comorbid with hyperlipidemia and combination of oral and injectable antidiabetic medications use were negatively associated with nonadherence to antidiabetic medications. Inpatients prescribed injectable antidiabetic medications were positive associated with poor glycemic control, while older inpatients and the presence of drug-related side effects were negative associated with poor glycemic control.ConclusionThe relatively low adherence and poor glycemic control among inpatients with T2DM in northwestern China highlighted the urgent need for effective strategies to improve adult diabetes management. Pharmacists should play an important role in strengthening social support to improve adult diabetes self-management.